Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2016)
Objectives: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. Method: In a randomized 10-week art intervention study with a pre-post follow-up-design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit-Test, and the Stick Test. Results: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time x Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. Conclusion: Mental stimulation by participation in art classes lead to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on psychological functioning across adulthood.
Keywords: subjective memory complaints; visual arts; mental stimulation; processing speed; visuo-spatial cognition

Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2017)
OBJECTIVES: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. METHOD: In a randomized 10-week art intervention study with a pre-post follow-up design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit Test, and the Stick Test. RESULTS: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time × Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. CONCLUSION: Mental stimulation by participation in art classes leads to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on cognitive abilities across adulthood.
EVALuna2:36362

The Impact of Perceived Knowledge of Dementia on Caregiver Burden - Schindler, Manuel; Engel, Sabine; Rupprecht, Roland (GeroPsych, 2012)
This study centered around 131 caregivers and their recipients to investigate whether the caregiver’s perceived knowledge of dementia may be a factor in reducing caregiver burden. We developed a questionnaire to measure this kind of knowledge. A significant relationship was shown between perceived knowledge and caregiver burden. Our multivariate analysis furthermore demonstrated that the caregivers’ self-assessed state of health also has a significant influence. A second regression model included the different aspects of perceived knowledge of our questionnaire and showed that certain aspects of perceived knowledge, especially concerning existing professional help services, noncognitive symptoms of dementia, and the importance of not neglecting one’s own personal needs, has an positive impact on caregiver burden.
Keywords: perceived knowledge; caregiver burden; dementia